Keeping Track: Options to Develop International Greenhouse Gas Unit Accounting after 2012 - Prag, Andrew (OECD Publishing, 2011)
This paper examines environmental and institutional implications of the use of tradable GHG units under different international accounting scenarios in the post-2012 international climate change policy framework. A range of possible scenarios is presented based on analysis on various building blocks for emissions accounting. On one side continuation of a Kyoto Protocol type accounting approach is considered with allocation of centrally-administered emissions allowances for Annex I countries. On the other side, a less centralised system is presented based on emission reduction pledges by countries. Aspects of these two scenarios are then combined to identify common elements in a middle ground scenario. The middle ground scenario presented would not use centrally-allocated emissions allowances but would retain some level of commonly-agreed accounting rules to ensure shared understanding of the content and scope of pledges, and to provide a stable platform for international use of offset units. The middle-ground scenario also envisages a role for UNFCCC bodies to set standards for new credit-based market mechanisms, and suggests that the existing International Transaction Log might be modified to track new unit types in addition to existing Kyoto Protocol units. Transparent tracking of units would help to minimize the risk of "double counting" of emissions reductions towards the emissions objective of more than one country
Keywords: Energy; Environment